Piperlongumine, a Potent Anticancer Phytotherapeutic, Induces Cell Cycle Arrest and Apoptosis In Vitro and In Vivo through the ROS/Akt Pathway in Human Thyroid Cancer Cells - Kung, Fang-Ping; Lim, Yun-Ping; Chao, Wen-Ying; Zhang, Yi-Sheng; Yu, Hui-I; Tai, Tsai-Sung; Lu, Chieh-Hsiang; Chen, Shu-Hsin; Li, Yi-Zhen; Zhao, Pei-Wen; Yen, Yu-Pei; Lee, Ying-Ray (Cancers, 2021)
Thyroid cancer (TC) is the most common endocrine malignancy, and its global incidence has steadily increased over the past 15 years. TC is broadly divided into well-differentiated, poorly differentiated, and undifferentiated types, depending on the histological and clinical parameters. Thus far, there are no effective treatments for undifferentiated thyroid cancers or advanced and recurrent cancer. Therefore, the development of an effective therapeutic is urgently needed for such patients. Piperlongumine (PL) is a naturally occurring small molecule derived from long pepper; it is selectively toxic to cancer cells by generating reactive oxygen species (ROS). In this study, we demonstrate the potential anticancer activity of PL in four TC cell lines. For this purpose, we cultured TC cell lines and analyzed the following parameters: Cell viability, colony formation, cell cycle, apoptosis, and cellular ROS induction. PL modulated the cell cycle, induced apoptosis, and suppressed tumorigenesis in TC cell lines in a dose- and time-dependent manner through ROS induction. Meanwhile, an intrinsic caspase-dependent apoptosis pathway was observed in the TC cells under PL treatment. The activation of Erk and the suppression of the Akt/mTOR pathways through ROS induction were seen in cells treated with PL. PL-mediated apoptosis in TC cells was through the ROS-Akt pathway. Finally, the anticancer effect and safety of PL were also demonstrated in vivo. Our findings indicate that PL exhibits antitumor activity and has the potential for use as a chemotherapeutic agent against TC. This is the first study to show the sensitivity of TC cell lines to PL.